BUDAYA BELAJAR SANTRI DAN DAMPAKNYA TERHADAP PENGEMBANGAN SUMBER DAYA MANUSIA DI PONDOK PESANTREN BANGKALAN - Al Aluf, Wilda; Maila Faiza HJ; Iriani Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explore the learning culture of students in Islamic boarding schools and analyze its impact on human resource development. Islamic boarding schools have become an important pillar of education in Indonesia, integrating religious and academic education to shape the character and skills of students. This research uses a qualitative approach with in-depth interviews and participatory observation to collect data from students, teachers, and administrative staff. The results show that typical pesantren learning methods, such as halaqah (group discussion) and muroja'ah (repetition of material), not only improve santri's understanding of religious material but also develop social skills, leadership, and work ethics. The disciplinary environment in pesantren has proven to be effective in shaping the independence and responsibility of santri. The conclusion of this study underscores the important role of Islamic boarding schools in developing soft skills needed in the modern world of work, thus contributing to improving the quality of human resources in Indonesia.